Digestibilidade de dietas e metabolismo de suínos alimentados com dietas contendo micotoxinas e organoaluminosilicato - Hauschild, Luciano (2007)
The objective of this document was to realize two studies to evaluate the digestibility of diets and metabolism of pigs fed with diets containing mycotoxins and organoaluminosilicate. In the first study it evaluated the diets and metabolic balance of piglets fed with diets containing 800 μg kg-1 of aflatoxins (AFLs). The experimental design utilized was completely randomized whit two treatments (control diet and control + 800 μg kg-1 AFLs), with four replications each, the animal was the experimental unit. The experimental period was 10 days. The digestibility coefficient of dry matter, protein and crude energy were not affected (P>0.05) by inclusion of 800 μg kg-1AFLs. The energy metabolization decreased 6% (P<0.05) on animals fed with diet containing aflatoxins. In N balance the N losses in urine increased 52% and the retention in relation the absorption reduced in 31% on animals fed with diet containing aflatoxins. Concerning the energy balance, the gross energy intake was not influenced (P>0.05) by the addition of AFLs in the diet. Energy losses in urine increased (P<0.05) 52% in the pigs fed diets containing aflatoxins. The presence of 800 μg kg-1 of AFLs in the diet did not affect the digestibility, but it altered the protein and energy metabolism of weaned piglets. In the second study it evaluated the digestibility of diets and metabolism of piglets fed with diets containing zearalenone (ZEA) with or without addition of organoaluminosilicate (OA). A completely randomized design was utilized whit three treatments (control, control + 2 mg kg-1 ZEA and control + 2 mg kg-1 ZEA with addition of 0,3% OA in diet), and four replications, the animal was the experimental unit. The experimental period was 16 days. The ZEA and the OA did not affect (P>0.05) the dry matter intake, dry matter and gross energy digestibility, metabolizable energy, energy and protein digestible. The N balance was not modified (P>0.05) by ZEA and organoaluminosilicate. However, it influenced (P<0.05) the fecal excretion of phosphorus. In diets containing ZEA and ZEA+OA the fecal excretion of P decreased 15 and 10% than control group. The ZEA and the OA did not affect (P>0.05) the P absorption in relation to the ingestion. The intake of 2 mg kg-1 of ZEA with or without addition of 0,3% OA in diet does not affect the diets digestibility and the pigs metabolism.